2019
DOI: 10.22469/jkslp.2019.30.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Validity and Reliability of Korean Version of the Aging Voice Index (KAVI)

Abstract: Background and Objectives:Voice disorder is recognized as a major problem because it negatively affects the elderly's social participation and quality of life. The purpose of this study was to examine the validity and reliability of Korean aging voice index (KAVI), which assesses the quality of life related to the voice of the elderly. Materials and Method:This study was conducted on 211 elderly people aged 65 years or older : 111 patients with voice disorder (mean age 69.8, range 65-80 years) and 100 nomorpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…Cronbach's alpha values of 0.9 or above can be considered desirable for clinical assessment tools. 34,35 Cronbach's alpha values of 0.949, 0.832, 0.83, 0.954, and 0.9733 were found for the original English AVI, 21 KAVI, 22 P-AVI, 23 A-AVI, 24 and CAVI in this study, respectively. indicated that all individual items of the CAVI were well correlated with the entire scale without the items themselves (Table 2).…”
Section: Reliability Of the Cavisupporting
confidence: 50%
See 4 more Smart Citations
“…Cronbach's alpha values of 0.9 or above can be considered desirable for clinical assessment tools. 34,35 Cronbach's alpha values of 0.949, 0.832, 0.83, 0.954, and 0.9733 were found for the original English AVI, 21 KAVI, 22 P-AVI, 23 A-AVI, 24 and CAVI in this study, respectively. indicated that all individual items of the CAVI were well correlated with the entire scale without the items themselves (Table 2).…”
Section: Reliability Of the Cavisupporting
confidence: 50%
“…Cronbach's alpha values of 0.9 or above can be considered desirable for clinical assessment tools 34,35 . Cronbach's alpha values of 0.949, 0.832, 0.83, 0.954, and 0.9733 were found for the original English AVI, 21 KAVI, 22 P‐AVI, 23 A‐AVI, 24 and CAVI in this study, respectively. These values of Cronbach's alpha indicated high internal consistency, especially for the original version, Arabic version, and the CAVI.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations